If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x(-2x + 1) = -11(x + 1) Reorder the terms: 6x(1 + -2x) = -11(x + 1) (1 * 6x + -2x * 6x) = -11(x + 1) (6x + -12x2) = -11(x + 1) Reorder the terms: 6x + -12x2 = -11(1 + x) 6x + -12x2 = (1 * -11 + x * -11) 6x + -12x2 = (-11 + -11x) Solving 6x + -12x2 = -11 + -11x Solving for variable 'x'. Reorder the terms: 11 + 6x + 11x + -12x2 = -11 + -11x + 11 + 11x Combine like terms: 6x + 11x = 17x 11 + 17x + -12x2 = -11 + -11x + 11 + 11x Reorder the terms: 11 + 17x + -12x2 = -11 + 11 + -11x + 11x Combine like terms: -11 + 11 = 0 11 + 17x + -12x2 = 0 + -11x + 11x 11 + 17x + -12x2 = -11x + 11x Combine like terms: -11x + 11x = 0 11 + 17x + -12x2 = 0 Begin completing the square. Divide all terms by -12 the coefficient of the squared term: Divide each side by '-12'. -0.9166666667 + -1.416666667x + x2 = 0 Move the constant term to the right: Add '0.9166666667' to each side of the equation. -0.9166666667 + -1.416666667x + 0.9166666667 + x2 = 0 + 0.9166666667 Reorder the terms: -0.9166666667 + 0.9166666667 + -1.416666667x + x2 = 0 + 0.9166666667 Combine like terms: -0.9166666667 + 0.9166666667 = 0.0000000000 0.0000000000 + -1.416666667x + x2 = 0 + 0.9166666667 -1.416666667x + x2 = 0 + 0.9166666667 Combine like terms: 0 + 0.9166666667 = 0.9166666667 -1.416666667x + x2 = 0.9166666667 The x term is -1.416666667x. Take half its coefficient (-0.7083333335). Square it (0.5017361113) and add it to both sides. Add '0.5017361113' to each side of the equation. -1.416666667x + 0.5017361113 + x2 = 0.9166666667 + 0.5017361113 Reorder the terms: 0.5017361113 + -1.416666667x + x2 = 0.9166666667 + 0.5017361113 Combine like terms: 0.9166666667 + 0.5017361113 = 1.418402778 0.5017361113 + -1.416666667x + x2 = 1.418402778 Factor a perfect square on the left side: (x + -0.7083333335)(x + -0.7083333335) = 1.418402778 Calculate the square root of the right side: 1.190967161 Break this problem into two subproblems by setting (x + -0.7083333335) equal to 1.190967161 and -1.190967161.Subproblem 1
x + -0.7083333335 = 1.190967161 Simplifying x + -0.7083333335 = 1.190967161 Reorder the terms: -0.7083333335 + x = 1.190967161 Solving -0.7083333335 + x = 1.190967161 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.7083333335' to each side of the equation. -0.7083333335 + 0.7083333335 + x = 1.190967161 + 0.7083333335 Combine like terms: -0.7083333335 + 0.7083333335 = 0.0000000000 0.0000000000 + x = 1.190967161 + 0.7083333335 x = 1.190967161 + 0.7083333335 Combine like terms: 1.190967161 + 0.7083333335 = 1.8993004945 x = 1.8993004945 Simplifying x = 1.8993004945Subproblem 2
x + -0.7083333335 = -1.190967161 Simplifying x + -0.7083333335 = -1.190967161 Reorder the terms: -0.7083333335 + x = -1.190967161 Solving -0.7083333335 + x = -1.190967161 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.7083333335' to each side of the equation. -0.7083333335 + 0.7083333335 + x = -1.190967161 + 0.7083333335 Combine like terms: -0.7083333335 + 0.7083333335 = 0.0000000000 0.0000000000 + x = -1.190967161 + 0.7083333335 x = -1.190967161 + 0.7083333335 Combine like terms: -1.190967161 + 0.7083333335 = -0.4826338275 x = -0.4826338275 Simplifying x = -0.4826338275Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.8993004945, -0.4826338275}
| F(-3)=x^4+3x^2+5 | | (11b-4)-5(2b+2)=-4 | | 6+2(7+x)=36+2y+10x | | 3=7y-5y-3 | | 4x+5y=-13 | | 14=-15x+4x | | 8x+6x+4+9=5x+5+8x | | 14=15x+4x | | 8=6y-4y | | 5x+11x=64 | | 3-x-7=3(x+1) | | n+5-5=12-5 | | 3-(5)-7=3((-5)+1) | | 3x^2-7+2=0 | | x+4(x-6)= | | 2(3x+2)=26 | | 4(-4)+8(-2)+3(-2)+6= | | -3.5x^2+40x+0=0 | | (-12-3)(-12-2)=(-12+5)(2*-12-3)+21 | | 7p+9=17+6p | | x^2-15x-76=0 | | (12-3)(12-2)=(12+5)(2*12-3)+21 | | -1+r=24 | | x^2-2x-3x+6=2x^2-3x+10x-15+21 | | 9+x=12 | | 9y-5=2 | | 4m+mn+12+3n=0 | | 2x(x+1)=5 | | -33+4x-5=4(-33+4x)-4 | | 4x-(8x+6)=5x-24 | | 4x-38=x-5 | | x-5+4x-38=EG |